Possible angina detected by the WHO angina questionnaire in apparently healthy men with a normal exercise ECG: coronary heart disease or not? A 26 year follow up study. (14th May 2004) - Bodegard, J; Erikssen, G; Bjornholt, J V; Thelle, D; Erikssen, J
Abstract : Objective: To determine whether men with possible angina (from their responses to the World Health Organization angina questionnaire) but a normal exercise ECG differ in long term rates of coronary heart disease events from men with no symptoms of angina. Design: During 1972–75, 2014 apparently healthy men aged 40–59 years underwent an examination programme including case history, clinical examination, exercise ECG to exhaustion, and various other tests. All men completed the WHO angina questionnaire. Subjects: Of 2014 men, 68 had possible angina, 1831 had no symptoms of angina, and 115 were excluded because they had definite angina or pathological exercise ECGs. All 68+1831 had normal exercise ECGs and none developed chest pain during the exercise test. Results: At 26 years, men with possible angina had a coronary heart disease mortality of 25.0% (17/68) v 13.8% (252/1831) among men with no symptoms of angina (p < 0.013). They also had a higher incidence of coronary artery bypass grafting (CABG) (p < 0.0004) and acute myocardial infarction (p < 0.026). The excess coronary heart disease mortality among men with possible angina only started after 15 years, whereas differences in CABG/acute myocardial infarction started early. Multivariate analysis including well recognised coronary heart disease risk factors showed that possible angina was an independent risk factor (relative risk 1.79, 95% confidence interval 1.26 to 2.10). Conclusions: Men with possible angina, even with a normal exercise test, have a greater risk of dying from coronary heart disease, having an acute myocardial infarct, or needing a CABG than age matched counterparts with no symptoms of angina.